Media religiosity as a new form of manifestation of religious consciousness: a psychological analysis of the phenomenon - Kostruba, Natalia (Psychological Prospects Journal, 2021)
Purpose. The aim of the article is theoretical analysis of the psychological features of media religiosity as a new form of manifestation of religious consciousness. Methods. To realize the purpose of the study, we used the methods of theoretical scientific research: analysis, synthesis, generalization, psychological modeling. Results. The paper show that general features of the media-religious picture of the world, including scale, hyper-symbolism, focus on the present, emotional saturation of messages. Religion in the media performs educational, communicative, therapeutic and promotional (advertising) functions. Media religiosity is a new form of religious activity and the functioning of religious consciousness, which arose due to the development of mass culture and mass media. Features of this type of religiosity: network principles of communication, blurs the boundaries between sacred, ritual and secular, secular, changes the individual’s religious identity. Media religiosity makes it possible to participate in online services from anywhere in the world and thus allows you to choose a religious direction without being attached to a particular territory or country. Media-religiosity consists of three components: cognitive (manifested as rational or irrational), emotional-motivational (focus on external or internal values) and behavioral (religious activity is active or passive). Conclusions. In general, we can conclude that media religiosity is a natural manifestation of the process of religion integration into the information society. We see prospects for further research the problem with the development of a standardized questionnaire to study the features of media religiosity.